Pemanfaatan Komunitas Mataholang Sebagai Sumber Belajar Sejarah Tingkat SMA Guna Mengembangkan Kesadaran Sejarah Berbasis Sejarah Publik - Muhammad Bintang Akbar; Didin Saripudin; Tarunasena Tarunasena (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
History learning materials to develop historical awareness can be obtained from utilizing various existing learning resources, one of which is the use of the Mataholang Bandung Community which is based on public history. The aim of this research is to determine the dynamics of the Mataholang Bandung Community and its use as a learning resource to develop historical awareness based on public history. This research approach is qualitative with a case study method. The data collection techniques used in this research were participant observation, in-depth interviews, and documentation studies. The research location is the community secretariat at Karees Village, Bandung City with the research subjects being coordinators, administrators/members, and community advisors. The results of this research are that the Mataholang Bandung Community can be used as a historical learning resource to develop historical awareness based on public history. The conclusion of the research is that the Mataholang Bandung Community raises historical material that is not even known to the public so that it can increase historical insight and this community helps diversify historical learning sources through the activities it holds so that the material in these activities can be used to enrich history learning in schools.. The research suggestion is that the Mataholang Bandung Community can collaborate officially with the Bandung City Government, Bandung City Education Office, Bandung City Culture & Tourism Office, and schools in Bandung City area and surroundings to diversify local historical material in Bandung City and surroundings so that it can be used as a source for learning history and as material for developing historical activities.